Down's syndrome child with subglottic stenosis : a case report - Abdullah, Kahairi; Raja Lope Ahmad, Raja Ahmad Al'konee; Lukman, Mohd Fahmi (Internet Scientific Publications, 2006)
An asymptomatic subglottic stenosis in Down’s syndrome can be missed. This problem will be manifested after the child had certain general anaesthesia procedure. We describe a Down’s syndrome child with subglottic stenosis (Cotton grade III) whom was diagnosed after underwent cardiac surgery for congenital heart disease which was successfully treated by endolaryngeal microscopic laser treatment.